2020
DOI: 10.1037/emo0000655
|View full text |Cite
|
Sign up to set email alerts
|

Past adversity protects against the numeracy bias in compassion.

Abstract: Past research has suggested that one problematic limitation of compassion is its seeming resistance to increase in response to growing numbers of targets in distress. This insensitivity to numeracy results in the dampening of compassion when faced with mass suffering. Given that emerging evidence suggests that facing past adversity in life may foster compassion and a general prosocial orientation, we explored whether those who have experienced greater adversity show a resistance to this numeracy bias. In a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 35 publications
3
31
0
Order By: Relevance
“…In addition to concerns about emotional exhaustion and effort, when people think that they lack the efficacy to address other’s needs, they choose to avoid empathic engagement (Cameron et al, 2019). In contrast, increased confidence in one’s empathic abilities enhances empathic engagement (Cameron et al, 2019; Lim & DeSteno, 2019; Sharma & Morwitz, 2016). Likewise, the belief that empathy is a skill that can grow through one’s efforts increases people’s willingness to empathize when it is challenging (e.g., toward a member of an out-group; Schumann, Zaki, & Dweck, 2014).…”
Section: Barriers To Compassion Without the Relational Starting Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to concerns about emotional exhaustion and effort, when people think that they lack the efficacy to address other’s needs, they choose to avoid empathic engagement (Cameron et al, 2019). In contrast, increased confidence in one’s empathic abilities enhances empathic engagement (Cameron et al, 2019; Lim & DeSteno, 2019; Sharma & Morwitz, 2016). Likewise, the belief that empathy is a skill that can grow through one’s efforts increases people’s willingness to empathize when it is challenging (e.g., toward a member of an out-group; Schumann, Zaki, & Dweck, 2014).…”
Section: Barriers To Compassion Without the Relational Starting Pointmentioning
confidence: 99%
“… 1. Although emotional exhaustion and lack of self-efficacy are distinct reasons why people avoid empathy, diverse affective and cognitive facets are likely intertwined in acts of prosocial behavior in ordinary life (Zaki & Ochsner, 2012). In support of the latter view, research has demonstrated that self-efficacy partially mediates an increase in compassion for an increasing number of others in need, suggesting additional psychological processes at play (Lim & DeSteno, 2019). Aversive feelings that accompany one’s perception of lacking self-efficacy may also contribute to empathic distress. …”
mentioning
confidence: 97%
“…Notes 1 Although emotional exhaustion and lack of self-efficacy are distinct reasons why people avoid empathy, diverse affective and cognitive facets are likely intertwined in acts of prosocial behavior in ordinary life (Zaki & Ochsner, 2012). In support of the latter view, research has demonstrated that self-efficacy partially mediates an increase in compassion for an increasing number of others in need, suggesting additional psychological processes at play (Lim & DeSteno, 2019). Aversive feelings that accompany one's perception of lacking self-efficacy may also contribute to empathic distress.…”
Section: Codamentioning
confidence: 97%
“…In addition to concerns about emotional exhaustion and effort, when people think that they lack the efficacy to address others' needs, they choose to avoid empathic engagement (Cameron et al, 2019). In contrast, increased confidence in one's ability to empathize and meet others' needs enhances empathic engagement (Cameron et al, 2019;Lim & DeSteno, 2019;Sharma & Morwitz, 2016). Also, the belief that empathy is a skill that can grow through one's efforts increases people's willingness to empathize when it is challenging (e.g., toward a member of an out-group; Schumann, Zaki, & Dweck, 2014).…”
Section: Barriers To Compassion Without the Relational Starting Pointmentioning
confidence: 99%
“…6]. Research in a variety of areas indicates that self-efficacy is an important element for inducing prosocial action (e.g., [40,41,42,43]). Importantly, in the context of the Empathy Selection Task, there is no request for action beyond empathizing itself (i.e., there is no one to help).…”
Section: Stripping Away Rewardsmentioning
confidence: 99%